Study of EGFR expression in tumor tissue in patients with locally advanced oral cavity cancer receiving cetuximab therapy - A. A. Lyanova; L. Yu. Vladimirova; E. P. Ulianova; A. E. Storozhakova; N. A. Abramova; I. L. Popova; M. A. Teplyakova; N. M. Tikhanovskaya; V. S. Myagkova; K. A. Novoselova; L. A. Ryadinskaya; L. K. Strakhova; et al. (Медицинский совет, 2020)
Introduction: Squamous cell carcinoma of the oral cavity is one of the most common head and neck cancers with an aggressive course and high mortality rates. The aim of the study was to determine the EGFR expression levels in tumor tissues in patients with squamous cell carcinoma of the tongue and oral mucosa depending on the efficacy of the therapy. Material and methods: The study included 60 patients with squamous cell carcinoma of the tongue and oral mucosa T3-4N0-1M0. The main group included 30 patients receiving chemotherapy (cisplatin/fluorouracil) in combination with targeted therapy with cetuximab. The control group included 30 patients receiving chemotherapy without cetuximab. Both groups were divided into two subgroups: sensitive and resistant. Results: In treatment-resistant patients of the main group with cetuximab, the average EGFR expression was twice lower than the initial levels (p = 0.0080) and 1.7 times higher than in treatment-resistant patients of the control group (p = 0.0157). In treatment-sensitive patients, the average EGFR expression was 19.8 times lower (p = 0.0020) than initial values and 14.9 times higher (p = 0.0067) than in treatment-sensitive controls. Conclusions: A natural decrease in the EGFR expression in tumor tissues due to the targeted therapy was revealed. However,  some patients were resistant to cetuximab, which dictates the need to search for predictors of targeted therapy efficacy in patients with locally advanced squamous cell carcinoma of the tongue and oral mucosa.